VANADYL ?-DIKETONATE COMPLEXES FOR PALM OIL EPOXIDATION WITH TBHP AND OXYGEN GAS AS OXIDANT - Sari Sinambela, Novita
Indonesia is the largest producer of crude palm oil. Palm oil is an essential oil for food, chemical and cosmetic products. Synthesis route for palm oil derivatives is very important to improve the economic value of palm oil. Epoxide palm oil (EPO) is one of the derivatives of palm oil products. EPO has an important role in the coating industry, lubricants, adhesives and resins. EPO is generally produced by oxidizing palm oil carbon double bond using hydrogen peroxide assisted with mineral acids and organic solvents. Epoxide synthesis using hydrogen peroxide can cause exotermic reactions and less selective toward epoxide results due to the ring opening of epoxide. The use of mineral acids is also less preferred because it can cause corrosion to the reactors.This research was conducted to produce formulations of epoxide synthesis without using organic solvent and mineral acids. The epoxidation reactions are conducted by catalyst vanadyl ?-diketonate complexes with series (i) VO(acac)2; (ii) VO(bzac)2; (iii) VO(bzbz)2; (iv) VO(bztf)2). Tert-butyl hydroperoxide (TBHP) is used as oxidant. Epoxidation reactions are also carried out with various types of oxo metals (ZnO, MgO, ZrOCl2, V2O3, V2O5 and MoO3) to evaluate the characteristics of the oxo metal corresponding to the reaction. Evaluation of oxo metal as catalyst found that epoxidation reaction can run well with metal ion which can be oxidized and minimum has one oxo ligand, oroxo metal at maximum oxidation number can be a catalyst if it has at least two oxo ligands. Palm oil epoxidation is estimated through a single electron transfer reaction. The results of cyclic voltammetry measurements of the oxovanadil ?-diketonate complex show that electron transfer can be carried out in this complex. Vis-spectroscopy measurements of the catalyst complex showed a change in the present of TBHP. The results of this measurement explain that the palm oil epoxidation reaction through oxidation of vanadium ion. Optimization of reaction parameters shows that the reaction is best at temperature 70 ?C, reaction time 7 h with catalyst concentration 0,14 mol% and 1,14 mol eq. TBHP. Observation of the reaction at a long time shows the formation of the epoxide ring opening product. Further research is carried out by replacing oxygen sources using O2 gas. The results of the study show that converting the TBHP oxidizer to O2 gas can obtainedepoxide with two different conformation that are trans and cis epoxide.